2017
DOI: 10.1103/physreva.96.013620
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dynamics of bosons in a two-ring ladder: Dynamical algebra, vortexlike excitations, and currents

Abstract: We study the quantum dynamics of the Bose-Hubbard model on a ladder formed by two rings coupled by tunneling effect. By implementing the Bogoliubov approximation scheme, we prove that, despite the presence of the inter-ring coupling term, the Hamiltonian decouples in many independent sub-HamiltoniansĤ k associated to momentum-mode pairs ±k. Each sub-HamiltonianĤ k is then shown to be part of a specific dynamical algebra. The properties of the latter allow us to perform the diagonalization process, to find ener… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 51 publications
(78 reference statements)
1
24
0
Order By: Relevance
“…one boson in an atomic species and one in the other) through the terms K ± . We remark that this second process is due to operators K± which were absent in the two-ring model [21]. Some of these microscopic processes are illustrated in Fig.…”
Section: A Energy Eigenstates and Eigenvaluesmentioning
confidence: 88%
See 1 more Smart Citation
“…one boson in an atomic species and one in the other) through the terms K ± . We remark that this second process is due to operators K± which were absent in the two-ring model [21]. Some of these microscopic processes are illustrated in Fig.…”
Section: A Energy Eigenstates and Eigenvaluesmentioning
confidence: 88%
“…In this article, using the method applied to the dynamics of bosons in a tworing ladder [21], we analyze the low-energy excitations in a two-component bosonic mixture described within the BH picture and confined on ring lattice. The ring geometry, designed more than ten years ago in [22], has recently raised a lot of interest in the study of atomtronic devices [23], [24] and its feasibility has been proved to be within the reach of current experimental techniques.…”
Section: Introductionmentioning
confidence: 99%
“…In this appendix, we derive, by means of a modified version of the Bogoliubov approximation scheme [32,43], the analytical expression of quasiparticles' frequencies of a L = 3-system when its ground state exhibits a supermixed soliton-like structure (namely, when it belongs to phase SM). In this circumstance, in fact, one can recognize that there are two site modes, a 1 , b 1 , that are macroscopically occupied, namely n 1 ≈ N a − n 2 − n 3 and m 1 ≈ N b − m 2 − m 3 while the microscopically occupied ones are a 2 , a 3 , b 2 and b 3 .…”
Section: Appendix Amentioning
confidence: 99%
“…In quasi-one-dimensional systems, analogs of the Meissner and Vortex phase have been predicted for the bosonic two-leg ladder [1][2][3][4][5], the simplest system where orbital magnetic field effects are allowed. It was shown that in this model, the quantum phase transition between the Meissner and the Vortex phase is a commensurate-incommensurate transition [6][7][8].…”
Section: Introductionmentioning
confidence: 99%